Telehealth in Cystic Fibrosis: Does the Integration of Modern Technology with Traditional Care Improve Health Related Outcomes? - Wood, Jamie (Curtin University, 2020)
The research conducted within this thesis investigated the integration of modern technology with traditional care in adults with cystic fibrosis (CF), and measured the impact on health outcomes. Specifically, videoconferencing was used to provide CF clinics to adults with CF living in rural and remote Western Australia (WA), and a smartphone application was developed to facilitate the detection of exacerbations in those living in both the metropolitan and rural and remote areas of WA.